2017
DOI: 10.1186/s13046-017-0534-0
|View full text |Cite
|
Sign up to set email alerts
|

FGF2/FGFR1 regulates autophagy in FGFR1-amplified non-small cell lung cancer cells

Abstract: BackgroundAutophagy is a conserved catabolic process to degrade cellular organelles. The role of autophagy in cancer development is complex. Amplification of fibroblast growth factor receptor 1 (FGFR1) is one of the most frequent targets in lung squamous cell carcinoma (SQCC). Whether fibroblast growth factor 2 (FGF2)/FGFR1 contributes to the regulation of autophagy remains elusive.MethodsAutophagic activity was evaluated by immunoblotting for microtubule-associated protein 1 light chain 3 (LC3), formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 55 publications
2
40
0
Order By: Relevance
“…Similarly, FGFR2 fusion genes that result in altered cell morphology and increased cell proliferation have been described in CCA [99]. It has been shown that FGFR alterations suppress autophagy, which could be associated with initial steps of carcinogenesis, and genetic or pharmacological FGFR inhibition in vitro induces protective autophagy in lung and breast cancer; therefore, inhibition of autophagy increases anticancer efficacy of FGFR inhibitors in these cells [100,101]. There are currently FGFR inhibitors in clinical development for CCA, opening the possibility of evaluating the combination of these inhibitors with autophagy modulators to increase efficacy.…”
Section: Cholangiocarcinoma Genetic and Epigenetic Alterations And Aumentioning
confidence: 95%
“…Similarly, FGFR2 fusion genes that result in altered cell morphology and increased cell proliferation have been described in CCA [99]. It has been shown that FGFR alterations suppress autophagy, which could be associated with initial steps of carcinogenesis, and genetic or pharmacological FGFR inhibition in vitro induces protective autophagy in lung and breast cancer; therefore, inhibition of autophagy increases anticancer efficacy of FGFR inhibitors in these cells [100,101]. There are currently FGFR inhibitors in clinical development for CCA, opening the possibility of evaluating the combination of these inhibitors with autophagy modulators to increase efficacy.…”
Section: Cholangiocarcinoma Genetic and Epigenetic Alterations And Aumentioning
confidence: 95%
“…Furthermore, consistent with our previous study, it was observed that PLCγ1 inhibition blocked mTOR and ULK1 phosphorylation in lung adenocarcinoma A549 cells, suggesting thereby that the suppression of PLCγ1/mTOR/ULK1 axis might contribute to PLCγ1 inhibition-driven autophagy. Activated ERK could regulate autophagy either positively or negatively [24][25][26]. Meanwhile, PLCγ1 regulation of ERK phosphorylation has been demonstrated previously [27,28].…”
Section: Discussionmentioning
confidence: 87%
“…Both Yuan et al . () and Chen et al . () found that blocking autophagy by knockdown of Beclin and ATG5 increased cell death by FGFR inhibition.…”
Section: Discussionmentioning
confidence: 96%
“…Autophagy has been previously reported in FGFR1‐amplified lung cancer models and a single breast cancer line following FGFR inhibition with AZD4547 (Yuan et al ., ) or PD166866, respectively (Chen et al ., ). In contrast to our findings in EC, FGFR inhibition in combination with either lysosomal protease inhibitors or chloroquine leads to a significant increase in lipidated LC3‐II or LC3 puncta in these lines, suggesting that FGFR inhibition increases autophagosome synthesis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation